Effect of counterions on comb-like polycarboxylate conformation in aqueous solutions. Issue 5 (4th May 2017) - Zhang, Qian; Ran, Qianping; Zhao, Hongxia; Shu, Xin; Yang, Yong
ABSTRACT: Laser light scattering (LLS) and conductivity experiments were performed to investigate the effect of counterions on the conformation of polycarboxylate comb-like copolymers (PCEs) in aqueous solutions. The addition of monovalent ions (i.e., Na + and K + ) to dilute polycarboxylate comb-like copolymer solutions induced a slight shrinking of the molecular chains because of the screening of electrostatic intramolecular repulsion. Varying complexation phenomena, such as the formation of intramolecular complexation at certain Ca 2+ concentrations and a transition between intermolecular and intramolecular complexations at different Ca 2+ concentrations, were closely associated with Ca 2+ concentration. Therefore, Ca 2+ exerted a more complex influence on the conformation of PCEs with side chains containing polyethylene oxide (PEO) with different grafting densities. In addition, various combination types of Ca 2+ with carboxylic groups were confirmed by theoretical simulation. GRAPHICAL ABSTRACT: